FALSAFAH HUMA BETANG DI KALIMANTAN TENGAH: SEBUAH PERGULATAN IDENTITAS KONSELOR DAYAK MUSLIM - Dody Riswanto (Institut Agama Islam Negeri Bengkulu, 2019)
The background of this research begins with the existence of Muslim Dayak counselors in schools who get a negative perception of the social environment regarding the existence of tribal counselors based on the religion adopted. This research method uses a qualitative approach where researchers act as key instruments, data collection techniques using interviews, observation, documentation studies and data triangulation, data analysis results from a combination of all data collection techniques that produce qualitative meanings and propositions. The negative perception of the social environment is the main problem of the formation of the identity of Muslim Dayak counselors that is strongly believed by the counselor, for which Muslim Dayak counselors need good communication skills in conveying their identities to the social environment so that the formation of self-identity can be done well. Overall Muslim Dayak counselors are able to introduce self-identity well without any obstacles based on the religion adopted. This happened partly because of the philosophy of Huma Betang which contained values of tolerance and mutual respect among religious believers who could reduce negative perceptions of the social environment about the existence of Muslim Dayak counselors.